IDEOLOGI DALAM BERITA POLITIK INDONESIA OLEH SYDNEY MORNING HERALD - Ribut Surjowati (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2013)
Abstract.  This article presents the analysis of the ideology in the headlines in Sydney Morning Herald which report political news in Indonesia. The writer would like to find out the ideology presented by Sydney morning Herald through the lexical choices and syntactical features while reporting Indonesia Political news  because it cannot be denied that Australia as the country where Sydney morning Herald was born, has some roles in the internal problem of Indonesia, therefore it is assumed that in reporting the news, this newspaper will be influenced by the situational context  and socio historical context where and when the news were written. The data used in this research is the headline of the news about Papua Conflict started from 2006 until 2012. The writer used CDA as a tool to reveal these ideologies. From 9 articles analyzed, the result of the study showed that mostly, according to SMH, Australia looked at the conflict of Papua as the complex problems which involved not only the Indonesia government. SMH gives negative evaluation towards the conflict there. SMH sees that Australia supports that humans have freedom to choose their own will, therefore, the writer sees that Australia supports Papuans to fight for their independence. Key terms:  Analisis wacana kritis, Sydney Morning Herald, Ideology